2015
DOI: 10.1136/annrheumdis-2013-204963
|View full text |Cite
|
Sign up to set email alerts
|

Sarilumab for the treatment of ankylosing spondylitis: results of a Phase II, randomised, double-blind, placebo-controlled study (ALIGN)

Abstract: ObjectivesThe ALIGN study (NCT01061723) evaluated the efficacy and safety of sarilumab, the first fully human monoclonal antibody against interleukin-6 receptor-α (IL-6Rα), in patients with ankylosing spondylitis (AS).MethodsPatients with active AS despite conventional treatment were randomised to placebo, or one of five subcutaneous dose regimens of sarilumab (100, 150 or 200 mg every other week, or 100 or 150 mg every week), for 12 weeks. The primary efficacy end point was the percentage of patients achievin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
73
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(83 citation statements)
references
References 28 publications
3
73
1
6
Order By: Relevance
“…[29][30][31][32][33] Although head-to-head trials would be required to fully assess the efficacy and safety of secukinumab versus TNF-inhibitors, the ASAS20 * Plus-minus values are means ±SD. The reporting period for safety data was the period from baseline to the visit at week 52 of the last patient enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] Although head-to-head trials would be required to fully assess the efficacy and safety of secukinumab versus TNF-inhibitors, the ASAS20 * Plus-minus values are means ±SD. The reporting period for safety data was the period from baseline to the visit at week 52 of the last patient enrolled.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomised, double-blind, placebo-controlled studies showed that the anti-IL6 agents tocilizumab and sarilumab are ineffective on AS [114,115].…”
Section: Other Drugs (Still Unapproved For the Use In Spa)mentioning
confidence: 98%
“…Moreover, up to 50% of patients with active axSpA do not achieve primary endpoints despite treatment with NSAIDs and/or anti-TNF-α blocking agents [56]**. Moreover, recent clinical trials also demonstrated that targeting other cytokines or molecules such as IL-1 [57], IL-6 [58], or enzyme phosphodiesterase 4 (PDE4) [59] are not effective in axSpA. Fortunately, results from clinical trials show that targeting the IL-23/IL-17 pathway holds great promise for treatment of axSpA (Figure 2).…”
Section: Targeting Il-23/il-17 Pathway For the Treatment Of Axial Spamentioning
confidence: 99%